Control contable de los activos biológicos bajo la sección 34 de las NIIF para PYMES y su rentabilidad del sector porcino - Tacuri Morales, Tamara Ximena (2021)
This research focuses on the study of accounting control over biological assets carried out in companies in the pig sector, the objective of the investigation is to diagnose the process carried out by these companies and how to apply the accounting regulations related to NIFF Section 34 to the pymes. With the applied methodology, it was possible to collect specific information on the performance of the organizations before the accounting control of biologicals and different results could be obtained that allowed to give the respective conclusions to the present investigation. With the aforementioned information, it was possible to determine that with respect to the current situation of the analyzed companies, it was possible to diagnose that they do apply the indicated accounting regulations, but present problems in terms of the recognition of the cost or the adequate determination of the amounts to be taken in account for fair value. In addition to mentioning that the technical knowledge sent by small and medium-sized companies regarding the IFRS Section 34 regulations for SMEs comprise the base; However, they have indicated that there are problems of understanding about the recognition of gain or loss for the biological asset when it has needed some special attention or inputs different from the others............